Structural characteristics and strain behavior of two-dimensional C3N : First principles calculations. (August 2018) - Shi, Li-Bin; Zhang, Yan-Yan; Xiu, Xiao-Ming; Dong, Hai-Kuan
Abstract: In this study, structural characteristics and strain behaviors of C 3 N are investigated by first principles calculations. First, we investigate the stacking behaviors of C 3 N, and find the most stable order. Then, the band structure of C 3 N is investigated. We attempt to explain the disagreements between theoretical and experimental band gaps by impurity phase and biaxial strain. The band alignment at α − Al 2 O 3 / C 3 N interface is presented. The valence band offset (VBO) and conduction band offset (CBO) are larger than 1.49 eV, which suggest that the interface is a promising candidate used on short channel transistors. Finally, the strain behavior of C 3 N is studied. It is found that the monolayer C 3 N at 273 K can withstand up to a strain level of ε = 12% for zigzag and armchair uniaxial strain, and ε = 10% for ab biaxial strain. The band edge position, effective mass and band gap under the strain are presented. The CBO increases with the strain, which suggests that appropriate tensile strain can effectively prevent the leakage current of the device. Our investigation can provide valuable information for insight into the novel C 3 N materials. Graphical abstract: Image 1